2020
DOI: 10.3390/ijerph17249552
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine and Its Downstream Metabolites in Maternal and Cord Sera: Biomarkers of Prenatal Smoking Exposure Associated with Offspring DNA Methylation

Abstract: Nicotine is a major constituent of cigarette smoke. Its primary metabolite in maternal and cord sera, cotinine, is considered a biomarker of prenatal smoking. Nicotine and cotinine half-lives are decreased in pregnancy due to their increased rate of metabolism and conversion to downstream metabolites such as norcotinine and 3-hydroxycotinine. Hence, downstream metabolites of nicotine may provide informative biomarkers of prenatal smoking. In this study of three generations (F0-mothers, F1-offspring who became … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 51 publications
0
7
0
1
Order By: Relevance
“…Keterpaparan asap rokok terhadap ibu yang sedang hamil sangat berpengaruh bagi janin yang dikandungnya dan dapat mengakibatkan bayi berat lahir rendah (BBLR) serta dapat mengakibatkan KJDR karena asap rokok yang dihirup oleh ibu hamil mengandung bahan kimia beracun antara lain, karbonmonoksida (CO) yang dihasilkan oleh asap rokok. Nikotin dalam asap rokok dicurigai sebagai neutrogen terhadap janin (23).…”
Section: Besar Risiko Keterpaparan Asap Rokok Dengan Kejadian Bblrunclassified
“…Keterpaparan asap rokok terhadap ibu yang sedang hamil sangat berpengaruh bagi janin yang dikandungnya dan dapat mengakibatkan bayi berat lahir rendah (BBLR) serta dapat mengakibatkan KJDR karena asap rokok yang dihirup oleh ibu hamil mengandung bahan kimia beracun antara lain, karbonmonoksida (CO) yang dihasilkan oleh asap rokok. Nikotin dalam asap rokok dicurigai sebagai neutrogen terhadap janin (23).…”
Section: Besar Risiko Keterpaparan Asap Rokok Dengan Kejadian Bblrunclassified
“…Secondly, studies on the association of PM 2.5 air pollutants and newborn birth weight outcomes suggested that the changes of oxidative stress ( 43 ), immune response ( 44 ), and epigenetic regulation ( 45 ) may influence birth weight. Furthermore, studies on the association of maternal tobacco smoke exposure and fetal birth weight suggested that placental toxicity ( 46 ) and epigenetic modifications, such as DNA methylation ( 47 ), could be potential mediators affecting fetal birth weight outcomes. So epigenetic modification could be an explanation for the interaction between maternal exposure to SHS and PM 2.5 air pollutants on the risk of macrosomia.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal blood samples were collected at the child's birth (predelivery) and were analyzed to measure metabolites, nutrients, and toxins (MNTs) using a data‐independent untargeted approach based on high‐resolution mass spectrometry coupled to varied sample introduction strategies (reversed‐phase liquid chromatography, hydrophilic interaction liquid chromatography, and flow‐injection analysis). Such an approached enabled a blind molecular profiling that does not require a priori knowledge of compound identities and is suitable for detecting a wide range of substances derived from environment, food, gut microbiome, and endogenous exposures 18,19 . Fucoxanthinol 3‐arachidate (nlp16.65_955.6949m_z) was measured using negative‐ion LC/high resolution MS on a Waters Xevo G2‐XS QTof mass spectrometer as its formate adduct ([M + formate] − ) as a continuous variable generated by the Progenesis QI software.…”
Section: Methodsmentioning
confidence: 99%
“…Such an approached enabled a blind molecular profiling that does not require a priori knowledge of compound identities and is suitable for detecting a wide range of substances derived from environment, food, gut microbiome, and endogenous exposures. 18,19 Fucoxanthinol 3-arachidate (nlp16.65_955.6949m_z) was measured using negative-ion LC/high resolution MS on a Waters Xevo G2-XS QTof mass spectrometer as its formate adduct ([M + formate] − ) as a continuous variable generated by the Progenesis QI software.…”
Section: Fucoxanthinol 3-arachidate Measurementmentioning
confidence: 99%